2006
DOI: 10.1007/s00418-005-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of FlAsH/Lumio Green in active mitochondria can be reversed by β-mercaptoethanol for specific staining of tetracysteine-tagged proteins

Abstract: Recent advances in the field of small molecule labels for live cell imaging promise to overcome some of the limitations set by the size of fluorescent proteins. We tested the tetracysteine-biarsenical labeling system in live cell fluorescence microscopy of reggie-1/flotillin-2 in HeLa and N2a cells. In both cell types, the biarsenical staining reagent FlAsH/Lumio Green accumulated in active mitochondria and led to mitochondrial swelling. This is indicative of toxic side effects caused by arsenic, which should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…The relatively small size of the tetracysteine tag (∼2 kDa) might not interfere dramatically with different functions of actin, although it has been shown that the fission yeast formin Cdc12p, which is required for formation of the contractile ring, excludes tetracysteinetagged fission yeast actin, suggesting very stringent structural requirements for formins to promote the elongation of actin filaments (Chen et al, 2012). Moreover, owing to potential chemical toxicity caused by the labeling reaction, such as the accumulation of FlAsH in active mitochondria (Langhorst et al, 2006), this technique might be better suited for short-term live-cell imaging.…”
Section: Visualization Of F-actin In Fixed Cells and Tissuesmentioning
confidence: 99%
“…The relatively small size of the tetracysteine tag (∼2 kDa) might not interfere dramatically with different functions of actin, although it has been shown that the fission yeast formin Cdc12p, which is required for formation of the contractile ring, excludes tetracysteinetagged fission yeast actin, suggesting very stringent structural requirements for formins to promote the elongation of actin filaments (Chen et al, 2012). Moreover, owing to potential chemical toxicity caused by the labeling reaction, such as the accumulation of FlAsH in active mitochondria (Langhorst et al, 2006), this technique might be better suited for short-term live-cell imaging.…”
Section: Visualization Of F-actin In Fixed Cells and Tissuesmentioning
confidence: 99%
“…One reason may be background presumably due to FlAsH binding to off-target cysteine-rich proteins (Stroffekova et al, 2001;Berens et al, 2005;Langhorst et al, 2006;Hearps et al, 2007), necessitating a postincubation step to reduce this background. Successful applications of this technology have used protocols similar to that originally reported for FlAsH (Perlman and Resh, 2006;Arhel et al, 2006;Roberti et al, 2007;Tour et al, 2007) but have not addressed the specificity issue to allow one- step labeling of any protein, especially those localized to cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we tried labeling cells expressing TC-PrPs with FlAsH by using protocols based on one published for labeling extracellular proteins (Adams et al, 2002). We failed to detect any TC-PrP-specific staining and observed very high background labeling as reported by others (Stroffekova et al, 2001;Berens et al, 2005;Langhorst et al, 2006;Hearps et al, 2007) (see Supplemental Figure 1). …”
Section: Ideal-labeling Of Cell Surface Tc-prp With Flashmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahan (2006) reviewed the use of quantum dots as Xuorescent probes for live-cell imaging and pointed to their potential, in combination with ultrasensitive imaging techniques, for the analysis of single molecules. Other small molecules can be used in live-cell imaging such as the Xuorescein arsenical helix binder (FlAsH) which has been used for investigating the dynamics of reggie-1/Xotillin-2 protein in cell culture (Langhorst et al 2006). They found that the biarsenical staining reagent FlAsH/Lumio Green accumulated in active mitochondria, resulting in mitochondrial swelling which limits the usefulness of this reagent for livecell imaging.…”
Section: Methods and Hardware Developmentsmentioning
confidence: 99%